Cvt18/Gsa12 Is Required for Cytoplasm-to-Vacuole Transport, Pexophagy, and Autophagy in Saccharomyces cerevisiae and Pichia pastoris - Guan, Ju (The American Society for Cell Biology, 2001)
Eukaryotic cells have the ability to degrade proteins and organelles by selective and nonselective modes of micro- and macroautophagy. In addition, there exist both constitutive and regulated forms of autophagy. For example, pexophagy is a selective process for the regulated degradation of peroxisomes by autophagy. Our studies have shown that the differing pathways of autophagy have many molecular events in common. In this article, we have identified a new member in the family of autophagy genes. GSA12 in Pichia pastoris and its Saccharomyces cerevisiae counterpart, CVT18, encode a soluble protein with two WD40 domains. We have shown that these proteins are required for pexophagy and autophagy in P. pastoris and the Cvt pathway, autophagy, and pexophagy in S. cerevisiae. In P. pastoris, Gsa12 appears to be required for an early event in pexophagy. That is, the involution of the vacuole or extension of vacuole arms to engulf the peroxisomes does not occur in the gsa12 mutant. Consistent with its role in vacuole engulfment, we have found that this cytosolic protein is also localized to the vacuole surface. Similarly, Cvt18 displays a subcellular localization that distinguishes it from the characterized proteins required for cytoplasm-to-vacuole delivery pathways.